Ultrafast all-optical generation of pure spin and valley currents - D. Gill; S. Sharma; J. K. Dewhurst; S. Shallcross (npj 2D Materials and Applications)
Abstract Pure currents comprise the flow of a two state quantum freedom – for example the electron spin – in the absence of charge flow. Radically different from the charge currents that underpin present day electronics, in two dimensional materials possessing additional two state freedoms such as valley index they offer profound possibilities for miniaturization and energy efficiency in a next generation spin- and valleytronics. Here we demonstrate a robust multi-pump lightwave protocol capable of generating both pure spin and valley currents on femtosecond times. The generation time is determined by the 2d material gap, with the creation of pure spin current in WSe2 at 40 fs and pure valley current in bilayer graphene at ~ 200 fs. Our all-optical approach demands no special material design, requiring only a gapped valley active material, and is thus applicable to a wide range of 2d materials.